Elaboration of Thermoresponsive Supramolecular Diblock Copolymers in Water from Complementary CBPQT4+ and TTF End‐Functionalized Polymers. Issue 4 (21st December 2013) - Sambe, Léna; Stoffelbach, François; Poltorak, Katarzyna; Lyskawa, Joël; Malfait, Aurélie; Bria, Marc; Cooke, Graeme; Woisel, Patrice; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> A well‐defined poly(N‐isopropyl acrylamide) 1 incorporating at one termini a cyclobis(paraquat‐p‐phenylene) (CBPQT4+) recognition unit is prepared via a RAFT polymerization followed by a copper‐catalyzed azide‐alkyne cycloaddition (CuAAC). 1H NMR (1D, DOSY), UV–vis and ITC experiments reveal that polymer 1 is able of forming effective host–guest complexes with tetrathiafulvalene (TTF) end‐functionalized polymers in water, thereby leading to the formation of non‐covalently‐linked double‐hydrophilic block copolymers. The effect of the temperature on both the LCST phase transition of 1 and its complexes and on CBPQT4+/TTF host–guest interactions is investigated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>